The Ethical Identity Index Based on Contemporary Maqaṣid al-Sharīʿah in Islamic Banking in Indonesia - Amimah Oktarina; Jaka Sriyana; Akhsyim Afandi; Abdul Hakim (Faculty of Sharia, UIN Jurai Siwo Lampung, 2026)
Ethical disclosure constitutes a central pillar of accountability in Islamic banking; however, existing measurement tools, particularly the Ethical Identity Index (EII), have not sufficiently captured recent developments in reporting practices within the Indonesian context. Prior studies predominantly employ static ethical frameworks, thereby limiting their responsiveness to evolving governance standards and contemporary interpretations of Islamic ethical principles. This study aims to address this gap by developing a Modified Sharia-Based Ethical Identity Index (MSBEII) grounded in Jasser Auda’s contemporary Maqaṣid al-Sharīʿah framework, which emphasises a dynamic, multidimensional approach to Islamic ethics. This research adopts a quantitative design by analysing annual reports of Islamic banks in Indonesia and comparing ethical disclosure quality before and after the implementation of the MSBEII. The Wilcoxon signed-rank test is utilised to examine statistically significant differences between disclosure scores derived from the original EII and the modified index. The findings demonstrate a significant improvement in ethical disclosure scores following the application of the MSBEII, indicating that the modified index is more sensitive in capturing previously underrepresented ethical dimensions, particularly those related to governance transparency, social responsibility, and value-based compliance. These results confirm that integrating a contemporary Maqaṣid al-Sharīʿah perspective enhances the analytical depth and contextual relevance of ethical disclosure measurement. Theoretically, this study contributes to advancing the Islamic banking literature by bridging the gap between normative Islamic ethical frameworks and empirical assessment tools. Practically, the MSBEII provides a more comprehensive and adaptable instrument for regulators, standard-setters, and industry practitioners to strengthen governance quality and ethical accountability.